2018
DOI: 10.1136/bmjopen-2018-022817
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the readiness of health facilities for diabetes and cardiovascular services in Bangladesh: a cross-sectional survey

Abstract: ObjectiveThe objective of this study was to assess the readiness of health facilities for diabetes and cardiovascular services in Bangladesh.DesignThis study was a cross-sectional survey.SettingThis study used data from a nationwide Bangladesh Health Facility Survey conducted by the Ministry of Health and Social Welfare in 2014.ParticipantsA total of 319 health facilities delivering services focused on diabetes and cardiovascular diseases (CVD) were included in the survey. Some of these facilities were run by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
60
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(75 citation statements)
references
References 18 publications
12
60
3
Order By: Relevance
“…The readiness of the health facilities in this study to offer DM services was less than optimal due to shortage of trained health workers, poor availability of supplies and medicines, inadequate guidelines and support systems for diabetes services. This finding is similar to what was reported by other, mostly cross-sectional studies, that assessed readiness and quality of diabetes care in Ethiopia [17], Bangladesh [18], Brazil [28] and Malawi [19]; where provision of diabetes services was greatly affected by lack of effective guidelines for diagnosis and management of diabetes, shortage of trained health workers and inadequate availability of medicines and equipment. In addition to these, a facility capacity assessment survey in Uganda [16] also found gaps in the availability of essential services and inadequate diagnostic capacity in most of the public sector facilities assessed.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The readiness of the health facilities in this study to offer DM services was less than optimal due to shortage of trained health workers, poor availability of supplies and medicines, inadequate guidelines and support systems for diabetes services. This finding is similar to what was reported by other, mostly cross-sectional studies, that assessed readiness and quality of diabetes care in Ethiopia [17], Bangladesh [18], Brazil [28] and Malawi [19]; where provision of diabetes services was greatly affected by lack of effective guidelines for diagnosis and management of diabetes, shortage of trained health workers and inadequate availability of medicines and equipment. In addition to these, a facility capacity assessment survey in Uganda [16] also found gaps in the availability of essential services and inadequate diagnostic capacity in most of the public sector facilities assessed.…”
Section: Discussionsupporting
confidence: 89%
“…However, care for chronic diseases is persistently affected by poor availability of equipment and essential medicines, limited diagnostic capacity, inadequate essential services and lack of standard guidelines [15, 16]. Similar gaps affect readiness of health systems in other developing countries like Ethiopia [17], Bangladesh [18] and Malawi [19].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, year round availability of essential medicines in Nepal was 16.6% in health facilities from the Mountains, 57.1% in the Hills, and 52.2% in the Terai [ 46 ]. A study in Bangladesh reported that the poor supply chain management for essential medicines affected the management of NCDs in the rural settings [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is a concern as Kasonde et al (2019) recently ascertained that several purchased medicines to manage non-communicable diseases (NCDs) in Bangladesh were expensive by international standards, with the least affordable being bisoprolol (for hypertension), metformin and atorvastatin, adding to concerns with affordability to treat family members with T2DM 28 . We are aware of ongoing plans in Bangladesh to reduce the prevalence and burden of NCDs; however, there are concerns with their implementation [29][30][31][32] . There are also currently high rates of smoking in Bangladesh, up to 35% of the adult population, highest among the South East Asian countries 11,[33][34][35] , adding to the cost and burden of NCDs 35,36 , which also needs to be addressed.…”
mentioning
confidence: 99%